Tipologias de estrutura de classe no Brasil: Discuss\~ao teórica, proposta metodológica e implicaç\~oes para as políticas públicas - Jo\~ao Cláudio Pompeu; Luís Carlos Garcia de Magalh\~aes; Carla Rodrigues Costa de Araújo; Yannick Kolai Zagbai Joel (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– The goal of this article is to analyse diferent teorethical and methodological approaches of classes structures typologies, the empírical metrics aplied in Brazil and their implications on public policies. Therefore, it is discussed the main theoretical currents that proposed the typologies and the metrics for the construction of class structures maps. Typologies and empirical methodologies are analyzed and applied to Brazilian case, proposed in the work of Santos (2002; 2015), Santos and Ribeiro (2016) and Souza and Carvalhaes (2014). Based on the critic evaluation of these authors, an initial methodological proposal is done in order to elaborate a class structure map for the Brazilian case.
Keywords: J62; Z10; Z13; 330; Brazilian society; social stratification; social class; economic dinamic; class map